2016
DOI: 10.1016/j.eti.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of two contrasting biochars on the bioaccessibility of 14C-naphthalene in soil

Abstract: This study investigated the impact of two different wood biochars (BioC1 and BioC2) on the extractability and biodegradation of 14 C-naphthalene in soil. Both biochars had contrasting properties due to difference in feedstocks and pyrolytic conditions (450-500 o C and 900-1000 o C, designated as BioC1 and BioC2, respectively). This study investigated effects of biochar on the relationship between 14 C-naphthalene mineralisation and calcium chloride (CaCl 2), hydroxypropyl-β-cyclodextrin (HPCD) or methanol extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…In soils with high TOC, PAHs tend to be sequestered over time thereby reducing their bioavailability/bioaccessibility to microbial degradation. 15,66,67 However, this depends on the composition, structure and pore distribution of organic matter, 44,68 which can delay the onset of mineralisation, hence longer lag phases. While this is true in the natural environment, the higher TOC content of the Norwegian soils is believed to be the factor responsible for the longer lag phases before the on-set of 14 C-phenanthrene.…”
Section: Discussionmentioning
confidence: 99%
“…In soils with high TOC, PAHs tend to be sequestered over time thereby reducing their bioavailability/bioaccessibility to microbial degradation. 15,66,67 However, this depends on the composition, structure and pore distribution of organic matter, 44,68 which can delay the onset of mineralisation, hence longer lag phases. While this is true in the natural environment, the higher TOC content of the Norwegian soils is believed to be the factor responsible for the longer lag phases before the on-set of 14 C-phenanthrene.…”
Section: Discussionmentioning
confidence: 99%
“…Prior extraction regime at each contact time (0, 25, 50, 100 d), the remaining 14 Cphenanthrene associated activity was determined through soil sample oxidation and the results showed that there was initial significant loss of activity. The initial loss of 14 Cphenanthrene activity between 0 and 25 days contact time of incubation was apparently mainly due to microbial degradation and to a minimal extent, volatilisation (Allan et al, 2006;Ogbonnaya et al, 2016). After the 25 days contact time, there was apparently no further loss of 14 C-phenanthrene activity through microbial degradation due to unavailability of the contaminant to biodegradation.…”
Section: Optimisation Of Xad Extractionmentioning
confidence: 95%
“…Single HP-β-CD extraction (20-22 h) successfully removes a combination of the rapidly desorbing and aqueously soluble (labile) fractions of LMW PAHs in soils by forming inclusion complexes within the hydrophobic cavity of HP-β-CD. This measurement can be valuable in predicting biodegradation endpoints in the assessment of contaminated land (Rhodes et al, 2012;Sanchez et al, 2013;Ortega-Calvo et al, 2015;Ogbonnaya et al, 2016). However, prediction of bioaccessibility has been less successful in larger soil organisms, such as earthworms, high molecular weight (HMW) PAHs contaminated soils and soils with relatively high amounts of black carbon (Hickman and Reid, 2005;Barther and Pelletier, 2007;Papadopoulos et al, 2007;Rhodes et al, 2012;Cui et al, 2013;Oyelami et al, 2014).…”
Section: Comparative Prediction Of 14 C-phenanthrene Biodegradabilitymentioning
confidence: 99%
“…However, these removal efficiencies are affected by some biochar and soil properties including the nature of pyrolysis, particle size and microbial community (Waqas et al 2015). For example, Ogbonnaya et al (2016) investigated the efficiency of wood-derived biochar made by slow pyrolysis and gasification and observed that biochar produced by slow pyrolysis was better at immobilizing 14 C-naphthalene in soil than biochar produced by gasification. This could be attributed to the presence of a larger amount of pores and organic functional groups on slowly pyrolysed biochar 450 -500 °C (ramped at 10 o C min -1 ) compared to gasified biochar at 900 -1000 °C.…”
Section: Polycyclic Aromatic Hydrocarbons (Pahs)mentioning
confidence: 99%